2016
DOI: 10.18632/oncotarget.6876
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-133b promotes the proliferation of human Sertoli cells through targeting GLI3

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 38 publications
0
57
0
Order By: Relevance
“…g . miR-137, miR-196a and miR-133b)123435. These data suggest that the AhR is a homeostatic regulator of basal miRNA expression.…”
Section: Discussionmentioning
confidence: 74%
“…g . miR-137, miR-196a and miR-133b)123435. These data suggest that the AhR is a homeostatic regulator of basal miRNA expression.…”
Section: Discussionmentioning
confidence: 74%
“…Considering the crucial role of immature SC in spermatogenesis, miRNAs act as important regulators in SC proliferation, maturation, and barrier regulation via the modulation of transcription factors involved in the cell cycle (Jiao et al, ; Ma et al, ; Yao et al, ). miR‐133b promoted SC proliferation by directly targeting the transcription factor GLI family zinc finger 3 and increased cyclin B1 and cyclin D11 expressions (Yao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific expression of miRNAs is found in different periods of mouse testes through gene chip and miRscan, and it has been confirmed that follicle stimulating hormone and androgen can regulate male reproductive activity through the expression of miRNAs in SCs (Mishima et al, ; Nicholls et al, ; Wu, Bao, Wang, Hu, & Xu, ; Yan et al, ). Recent studies have demonstrated that miRNAs repress the expression of SC target genes, thereby regulating SC proliferation, maturation, apoptosis, blood‐testis barrier, and stages of the seminiferous epithelium cycle (Jiao et al, ; Ma et al, ; Yao et al, ). Specific knockdown of Dicer, a central component of RNA interference machinery, downregulates the expression of several key genes in SCs and results in male infertility because of spermatozoa absence and progressive testicular degeneration (Papaioannou et al, ; Papaioannou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, using spermatogonial stem cell line C18-4, we have successfully demonstrated that Nodal plays an essential role in promoting the self-renewal of mouse SSCs via Smad2/3 pathway and Pou5f1 activation (He et al 2009) and GDNF stimulates the proliferation and survival of mouse SSCs by activating Ras/ERK1/2 signaling pathway and transcription factor Fos (He et al 2008). In addition, we have shown that miRNA-133b is uninvolved in the regulation of the human SSCs using a human SSC line (Hou et al 2015) and it specifically enhances the proliferation of human Sertoli cells (Yao et al 2016). Sertoli cell lines, e.g.…”
Section: Spermatocyte Line Immortalized With a Specific Promoter-basementioning
confidence: 98%
“…The establishment of male germ cell and Sertoli cell lines brings new promise for reproductive and regenerative medicine due to the great plasticity of spermatogonia and Sertoli cells. Human SSCs including spermatogonia can differentiate into male gametes (Yang et al 2014a), dedifferentiate to pluripotent ES-like cells (Golestaneh, et al 2009), and transdifferentiate to functional and mature hepatocytes (Chen et al 2016). Therefore, they may bring inspirations for new therapeutic strategies to cure male infertility patients with spermatogonia and other human diseases (e.g.…”
Section: Spermatocyte Line Immortalized With a Specific Promoter-basementioning
confidence: 99%